2017
DOI: 10.5194/tc-2017-180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulating the roles of crevasse routing of surface water and basal friction on the surge evolution of Basin 3, Austfonna ice-cap

Abstract: Abstract. The marine-terminating outlet in Basin 3, Austfonna ice-cap has been accelerating since the mid-1990s.Step-wise multiannual acceleration associated with seasonal summer speed-up events was observed before the outlet enters the basinwide surge in autumn 2012. We use multiple numerical models to explore hydrologic activation mechanisms for the surge behavior. A continuum ice dynamic model is used to invert basal friction coefficient distributions using the control method and observed surface velocity d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Our model experiments do not include seasonal cycles, but the predicted impact of surface water input is consistent with the observed timing and location of rapid speed-up events during surges. In Svalbard, several studies have shown that expansion of crevasse fields during the early stages of surges has created templates for areas of flow acceleration at ablation season onset (Dunse and others, 2015; Sevestre and others, 2018; Gong and others, 2018; Benn and others, 2019). The role of surface-to-bed drainage in stabilizing the flow is illustrated by Kronebreen, a perennially fast-flowing tidewater glacier in the midst of the Svalbard surge cluster.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Our model experiments do not include seasonal cycles, but the predicted impact of surface water input is consistent with the observed timing and location of rapid speed-up events during surges. In Svalbard, several studies have shown that expansion of crevasse fields during the early stages of surges has created templates for areas of flow acceleration at ablation season onset (Dunse and others, 2015; Sevestre and others, 2018; Gong and others, 2018; Benn and others, 2019). The role of surface-to-bed drainage in stabilizing the flow is illustrated by Kronebreen, a perennially fast-flowing tidewater glacier in the midst of the Svalbard surge cluster.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Nested models would allow selective high resolution of the processes that control folding and thrusting. Likewise, hybrid models such as that of Gong et al (), which combines a finite‐element full‐Stokes thermomechanical flow model with a discrete‐element treatment of ice fracture, hold promise.…”
Section: Discussionmentioning
confidence: 99%
“…Meltwater in crevasses has been implicated in initiating the conditions necessary for a surge, following an examination of a surge in "Basin 3" in Austfonna, an ice cap in Svalbard (Gong et al, 2018). Ice velocities began increasing in the mid-1990s as a result of basal meltwater production and crevasse formation.…”
Section: Structurally Controlled Hydrology Of Valley Glaciers and Ice Capsmentioning
confidence: 99%